Multifactor clinical-laboratory valuation of endogenic intoxication in chronic hepatitis B - N. I. Khokhlova; N. P. Tolokonskaya; A. B. Pupyshev (Бюллетень сибирской медицины)
For the determining of the role of clinical data and integral laboratory indices in the valuation of endogenic intoxication (EI) in chronic hepatitis B (HHB) 100 patients and 20 healthy adults were examined. The present symptoms of the disease and the facts about the character and communication of somatic diseases were studied and the effective concentration of albumin (ECA) and the reserve of albumin binding (RAB) were defined by fluorescence method twice at 18—20 days interval. The lowering of average indices of ECA and RAB was revealed in HHB patients in comparison with control group (p < 0,05), and this lowering was stable during the treatment. ECA and RAB levels reducing was more marked in HHB patients with negative changes of acute infectious diseases character and in patients with definite chronic somatic diseases in comparison with the opposite groups (p < 0,05).